Documenting adaptations to an evidence-based intervention in 58 resource-variable pediatric oncology hospitals across implementation phases - Alejandra Catalina Quesada-Stoner; Sayeda Islam; Amela Siječić; Sara Malone; Maria F. Puerto-Torres; Adolfo Cardenas; Kim Prewitt; Yvania Alfonso Carreras; Shilel Y. Alvarez-Arellano; Deiby Argüello-Vargas; Gloria I. Ceballo-Batista; Rosdali Diaz-Coronado; et al. (Implementation Science Communications)
Abstract Background Adaptation of evidence-based interventions (EBIs) often occurs when implemented in new local contexts and settings. It is unclear, however, during which phase of implementation adaptations are most frequently made and how these changes may impact the fidelity, effectiveness, and sustainability of the EBI. Pediatric Early Warning Systems (PEWS) are EBIs for early identification of deterioration in hospitalized children with cancer. This study evaluates adaptations of PEWS made among resource-variable pediatric oncology hospitals in Latin America implementing and sustaining PEWS. Methods We conducted a cross-sectional survey among pediatric oncology centers participating in Proyecto Escala de Valoración de Alerta Temprana (EVAT), a collaborative to implement PEWS. Adaptations to PEWS were assessed via 3 multiple choice and 1 free text question administered as part of a larger study of PEWS sustainability. Descriptive statistics quantitatively described what, when, and why adaptations were made. Qualitative analysis of free text responses applied the Framework for Reporting Adaptations and Modifications Expanded (FRAME) to describe respondent perspectives on PEWS adaptations. Results We analyzed 2,094 responses from 58 pediatric oncology centers across 19 countries in Latin America. Participants were predominantly female (82.5%), consisting of nurses (57.4%) and physicians (38.2%) who were PEWS implementation leaders (22.1%) or clinical staff (69.1%). Respondents described multiple PEWS adaptations across all implementation phases, with most occurring during the planning and piloting of EBIs. Adaptations included changes to PEWS content (algorithm, scoring tool, terminology, and use frequency) and context (personnel delivering or population). Respondents felt adaptations streamlined monitoring, enhanced effectiveness, improved workflow, increased comprehension, and addressed local resource limitations. Qualitative analysis indicated that most adaptations were categorized as fidelity consistent and planned; fidelity inconsistent adaptations were unplanned responses to unanticipated challenges. Conclusion Adaptations made to PEWS across implementation phases demonstrate how EBIs are adapted to fit dynamic, real-world clinical settings. This research advances implementation science by highlighting EBI adaptation as a potential strategy to promote widespread implementation and sustainability in hospitals of all resource levels.